Significance of quality of care for quality of life in persons with dementia at risk of nursing home admission: a cross-sectional study - Christina Bökberg; Gerd Ahlström; Staffan Karlsson (BMC, 2017)
Abstract Background Quality of life in persons with dementia is, in large part, dependent on the quality of care they receive. Investigating both subjective and objective aspects of quality of care may reveal areas for improvement regarding their care, which information may ultimately enable persons with dementia to remain living in their own homes while maintaining quality of life. The aim of this study was to 1) describe self-reported quality of life in persons with dementia at risk of nursing home admission. 2) describe subjective and objective aspects of quality of care, 3) investigate the significance of quality of care for quality of life. Methods A cross-sectional interview study design was used, based on questionnaires about quality of life (QoL-AD) and different aspects of quality of care (CLINT and quality indicators). The sample consisted of 177 persons with dementia living in urban and rural areas in Skåne County, Sweden. Descriptive and comparative statistics (Mann-Whitney U-test) were used to analyse the data. Results Based upon Lawton's conceptual framework for QoL in older people, persons with pain showed significantly lower quality of life in the dimensions behavioural competence (p = 0.026) and psychological wellbeing (p = 0.006) compared with those without pain. Satisfaction with care seemed to have a positive effect on quality of life. The overall quality of life was perceived high even though one-third of the persons with dementia had daily pain and had had a weight loss of ≥4% during the preceding year. Furthermore, 23% of the persons with dementia had fallen during the last month and 40% of them had sustained an injury when falling. Conclusion This study indicates need for improvements in home care and services for persons with dementia at risk for nursing home admission. Registered nurses are responsible for nursing interventions related to pain, patient safety, skin care, prevention of accidents, and malnutrition. Therefore, it is of great importance for nurses to have knowledge about areas that can be improved to be able to tailor interventions and thereby improve quality of care outcomes such as quality of life in persons with dementia living at home.